2021
DOI: 10.5006/3741
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Additively Manufactured Stainless Steels—Process, Structure, Performance: A Review

Abstract: The corrosion of additively manufactured (AM) metallic materials, such as stainless steels (SS), is a critical factor for their qualification and reliable use. This review assesses the emerging knowledgebase of powder-based laser AM SS corrosion and environmentally assisted cracking (EAC). The origins of AM-unique material features and their hierarchal impact on corrosion and EAC are addressed relative to conventionally processed SS. The effects of starting material, heat treatment and surface finishing are su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 187 publications
(319 reference statements)
1
12
0
Order By: Relevance
“…A plausible explanation for the postheat treatment reduced localized corrosion resistance is that irregularly shaped larger size postheat treatment inclusions could act as microcrevice sites, facilitating localized corrosion, 51 although further research is needed on this. A similar effect has been reported on the effects of porosity as reviewed in Schindelholz, et al 18 Independently of the role of inclusions, the repassivation potential of the samples-which depends on the extent of pitting/crevice corrosion but it is independent of the presence of inclusions 52 -were almost identical, suggesting a similar repassivation behavior regardless of the fabrication method and heat-treatment route. Likewise, PPM data confirmed a similar repassivation behavior.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…A plausible explanation for the postheat treatment reduced localized corrosion resistance is that irregularly shaped larger size postheat treatment inclusions could act as microcrevice sites, facilitating localized corrosion, 51 although further research is needed on this. A similar effect has been reported on the effects of porosity as reviewed in Schindelholz, et al 18 Independently of the role of inclusions, the repassivation potential of the samples-which depends on the extent of pitting/crevice corrosion but it is independent of the presence of inclusions 52 -were almost identical, suggesting a similar repassivation behavior regardless of the fabrication method and heat-treatment route. Likewise, PPM data confirmed a similar repassivation behavior.…”
Section: Discussionsupporting
confidence: 81%
“…16 The different manufacturing routes and the resulting microstructure appear to have a crucial role in the electrochemical-mechanical behavior of stainless steels. [17][18] Selective laser melting (SLM)-or powder-bed laser fusion additive manufacturing-allows layer-by-layer fabrication of solid metallic parts and components. Type 316L stainless steel is among the alloys that can be manufactured with SLM, and it has been the subject of many investigations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific microstructures 18 and numerous defects 4,5 encountered in LPBF 316L SS require classification beyond just an incremental variation of the conventional, well-annealed 316L SS (referred to hereafter as CWA 316L SS). 42,43 For example, the Mn-rich sulfides that play a major role in pitting initiation in CWA 316L SS [44][45][46] are not present in the LPBF material due to the rapid solidification and cooling that prevent this phase from forming. 23,47,48 Thus, pit nucleation operates under a different dominant mechanism.…”
Section: Corrosion Mechanisms In Lpbf 316l Ssmentioning
confidence: 99%
“…106 Investigations of the influence of melt pool boundaries on localized pitting corrosion of L-PBF 316L in chloride solutions are still limited. 43 However, recent reports 34,107 have shown that they could be preferential nucleation sites for pits, likely due to the local variation in elemental distribution, porosity, or residual stress. Using potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) tests coupled with optical microscopy and SEM of corroded surfaces, Zhao et al 107 showed that, regardless of the surface orientation, pit initiation was found to primarily occur at melt pool boundaries.…”
Section: Melt Pool Boundariesmentioning
confidence: 99%